REMOTE DATA ACQUISITION USING LOCAL AREA NETWORK (LAN) - MAT SOM, SITI RAHAYU (Universiti Teknologi PETRONAS, 2007)
This project is about remote control, data acquisition, data management and security system called as Remote Data Acquisition System Using Local Area Network (LAN). This system encompasses collection of information, method of transfer from the laboratory, analysis and control of the system, and display of the received information. This system has the capability to monitor and control laboratory operations in real time. By using this system, the user can control and collect data from any computer as the user login with assigned usemame and password using LAN in Universiti Teknologi PETRONAS. For this project, the methodology and project works are more on the design and execution works. The works related with programming the system, interfacing with LAN and the reliability and precision in the data collection and storage. The system will assist the user with systematic time management. Since both data collection and storage can be simultaneously done, this will increase efficiency as less manpower, time and energy will be utilized. It also provides the user the flexibility to use the system from any place and time.